2008
DOI: 10.1007/s00436-008-1104-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pathology of camel filariasis in Iran

Abstract: A total of 1,070 camels of different ages and of both sexes slaughtered at Mashhad slaughterhouse were inspected for infection with Dipetalonema evansi. Microfilariae were found in peripheral blood smears of 221 (20.7%) camels (14% females and 23% males). In a second study, the testicles, epididymises, spermatic cords, and lungs of 197 male camels were examined, and 165 (83.7%) were infected with adult forms of D. evansi. Tissue sections from 30 infected and ten uninfected camels were collected and processed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 12 publications
(8 reference statements)
12
32
0
1
Order By: Relevance
“…This result was in agreement with Musa et al [7] but it was higher as compared with the result of Oryan et al [20] which shown the minimum and maximum numbers of C. titillator found per camel were 6 and 136 respectively with a mean of 23.2 larvae per camel in cold seasons and 3 and 74 with a mean of 14.4 for warm seasons, and according to Arabali and Amare the minimum and maximum numbers of C. titillator larvae counted were 5 and 70 respectively [16].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result was in agreement with Musa et al [7] but it was higher as compared with the result of Oryan et al [20] which shown the minimum and maximum numbers of C. titillator found per camel were 6 and 136 respectively with a mean of 23.2 larvae per camel in cold seasons and 3 and 74 with a mean of 14.4 for warm seasons, and according to Arabali and Amare the minimum and maximum numbers of C. titillator larvae counted were 5 and 70 respectively [16].…”
Section: Discussionsupporting
confidence: 93%
“…This finding agrees with Bekele, Shakerian et al, El-Rahman and Oryan et al who reported that the prevalence of C. titillator larvae infestation was lower in younger camels and significantly higher in older camels [19,20,22,23]. It was documented that older camels may be more tolerant of flies and allow the deposition of egg around the nostrils; while the younger camels actively seek to prevent the flies settling around the nostrils [23].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations